'El Oeste en el Este': hacia una historia de la Història de Jacob Xalabín. - KOTSALÁS, LAMBROS (Scripta, 2017)
An adventure romance of a mostly oriental setting written in Catalan by an anonymous author of the Late Middle Ages. As it is clear from my research carried out on the primary sources, under the surface of the literary work in question unfolds the drama of the very last years of the so-called 'county' of Catalan-Byzantine Sola, that is, Salona, in the central Greece region of Phocis before the ottoman invasion (1394).